The Strength of Social Coding Collaboration on GitHub - Alves, Gabriela B.; Brandão, Michele A.; Santana, Diogo M.; da Silva, Ana Paula C.; Moro, Mirella M. (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2016: Anais do XXXI Simpósio Brasileiro de Bancos de Dados, 2016)
Social coding is an approach of software development that enables cooperation among developers. Specially, GitHub can be modeled as a social coding network and its study allows the discovery of relevant patterns, e.g., the collaborations strength. Finding such patterns may help to improve the recommendation of developers and the evaluation of team formation. Here, our goal is to analyze the correlation between network properties and such strength.